Matriks dan Pengukuran Terhadap Kinerja Tata Kelola Teknologi Informasi - Maniah - (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
IT Governance is a function organizations run by leaders, top management and IT management who jointly monitor the implementation of IT strategies to ensure harmony between businesses and IT [1]. This paper will answer the question -